Qualitative and quantitative metabolomics of Pamburus missionis Swingle – a medicinal tree taxon - Yaswanthi, M. Sai; Pallavi, P. N.; Savithramma, N. (Journal of Medicinal Herbs and Ethnomedicine, 2024)
Since ancient times, Plant based medicine is a well-known oldest form of healthcare to mankind. Even the commercial medications used for the treatment of various ailments today, contains a large proportion of plant derived chemical compounds. Hence chemical profiling of medicinal plants gained a key role to use them in pharmaceuticals as well as commercial industries. Pamburus missionis is one of the medicinal plants used in the Indian and Srilankan traditional medicine system to reduce kapha dosha. The ayurvedic physicians used its leaves to treat swelling, piles, fractures, fistula, puerperal diseases and as serpent venom. Therefore, the present study was undertaken to reveal the phytocompounds from various parts of this plant. Metabolomics revealed the presence of primary and secondary metabolites like carbohydrates, lipids, proteins, alkaloids, phenols, flavonoids, steroids etc. From the aqueous extract, Alkaloid content is almost same in leaf, stem and bark extracts with around 1.2 to 1.3 g (w/v%) and completely absent in the fruit. Phenolic content and steroids are notably high in leaf extract with 112.77±0.34 mg/g of extract and 17.91±0.26 mg respectively, where the flavonoid content in fruit extract with 44.69±0.30 mg/g of extract and the tannin content in bark extract with 62.37±1.75 mg/g of extract.